Synthesis of novel CoBiTi LDH and fabrication of LDH-LDO 3D-Heterojunction for enhanced infrared induced water splitting to hydrogen. (15th March 2022) - Mostafa, Mohsen S.; Lan, Chen; Selim, Mohamed S.; Ruiyi, Zhang; Ya, Gao; Shuai, Zhang; Ge, Guanglu
Abstract: The climate changes due to the long dependence on fossil fuel as the main energy source needs to discover alternative technologies for production of green fuels. Photocatalytic water splitting to hydrogen is a potential technology to achieve this challenge goal, but the process is still far from industrial application due to the weak activities of the fabricated catalysts of wide bandgap energies. Here, novel 1D CoBiTi layered double hydroxide (CBT-LDH) with a bandgap of 2.4 eV has been synthesized by a facile route and achieved hydrogen evolution rate (HER) of 272.8 μmolg −1 h −1 without scavengers. Due to doping with highly active Bi, 2D CoBiTi layered double oxide (CBTO) with high infrared (IR)-responsivity (bandgap = 1.27 eV) has been made by drying 1D CBT-LDH at 150 °C, which can achieve 113 μmolg −1 h −1 in the presence of a scavenger. However, in-situ compositing CBT-LDH and CBTO can fabricate novel 3D-heterojunction and duplicate the HER by 5 folds (∼1255 μmolg −1 h −1 ) under Xenon light irradiation. The novel 3D-heterojunction can effectively quench the recombination of the photoexcited species by the functional groups from CBT-LDH and cause a strong synergy between the visible and IR irradiation as a promising route for industrial hydrogen production. Graphical abstract: Image 1 Highlights: Novel CoBiTi LDH (CBT-LDH) were prepared and easily oxidized at 150 °C to CBTO. A novel heterojunction by CBT-LDH and CBTO was successfully prepared. A novel strategy to boost solar-induced hydrogen generation is introduced. High HE-rate by ∼5 folds could be achieved by a narrow bandgap without scavengers. CBT-LDH/CBTO prompts the upcoming strategy for alternative fuel production.